2018
DOI: 10.5194/os-14-1567-2018
|View full text |Cite
|
Sign up to set email alerts
|

The short timescale variability of the oxygen inventory in the NE Black Sea slope water

Abstract: Warm winters have recently become common over the Black Sea, leading to the risk of shoaling oxygen penetration. The insufficient supply of oxygen to the near-bottom layer may result in a decrease in faunal abundance. However, there is a lack of data on the temporal variations in oxygen throughout the water column over short timescales of hours to weeks. In this paper, new observations over the upper part of the NE Black Sea continental slope are presented. Regular, frequent measurements were performed using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Compared with the open ocean conditions, there are only two migrating copepods in the Black Sea, and their diel vertical migration depths are rather shallow, less than 120 m (Morozov et al, 2020). In the winter, the Black Sea oxic zone is usually ventilated due to surface cooling, turbulent mixing, and deep convection (e.g., Ostrovskii et al, 2018). The vertical gradients of dissolved oxygen vary greatly in the winter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the open ocean conditions, there are only two migrating copepods in the Black Sea, and their diel vertical migration depths are rather shallow, less than 120 m (Morozov et al, 2020). In the winter, the Black Sea oxic zone is usually ventilated due to surface cooling, turbulent mixing, and deep convection (e.g., Ostrovskii et al, 2018). The vertical gradients of dissolved oxygen vary greatly in the winter.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen stratification is sometimes characterized by the fall from approximately 300 to 10 μM across a 40 m thick layer (Ostrovskii et al, 2018). Such conditions would be a substantial barrier for the vertical migration of zooplankton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the characterization of Black Sea coastal eddies thus remains a technical challenge which, in particular, limits our capacity to characterize their contribution in the Black Sea biogeochemical cycles. Indeed, novel high-frequency observations obtained by tethered (Ostrovskii and Zatsepin, 2011;Ostrovskii et al, 2018) and free-floating profilers (Stanev et al, 2013;Akpinar et al, 2017) revealed that mesoscale eddies and their interaction with the shelf-slope may substantially influence the biogeochemical balance of the Black Sea by inducing diapycnal mixing events. As vertical oxygen transport is limited in the Black Sea by a sharp pycnocline, diapycnal mixing in the basin periphery may act as a net flux of oxygen to intermediate layers, thereby enabling horizontal diffusion (i.e., along isopycnals) towards the basin interior (Ostrovskii and Zatsepin, 2016).…”
Section: Mesoscale Circulation In the Black Seamentioning
confidence: 99%